(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2022)
Background: Regularly updated data on stroke and its pathological types, including data on its incidence, prevalence, mortality, disability, risk factors, and epidemiological trends, are essential for evidence-based stroke care planning and resource allocation. The study aimed to determine the sociodemographic features, risk factors, and outcomes of stroke patients admitted to a tertiary hospital in Chattogram, Bangladesh. Materials and methods: This prospective observational study include purposively selected 308 admitted stroke patients from the Department of Neurology of Chittagong Medical College Hospital (CMCH) from January 1, 2022, to April 31, 2022. Subgroup analysis between Ischemic Stroke (IS) and Hemorrhagic Stroke (HS) patients were done. Results: Mean age was 60.8 years and 52.9% were male. IS and HS was found respectively, among 78.9% and 21.1% of the patients. The most common risk factors were hypertension (76.3%) smoking (45.5%) diabetes (35.4%) dyslipidemia (33.1%) central obesity (28.2%) family history of stroke (24.4%) and ischemic heart disease (20.1%). Hypertension (p<0.001) and alcohol drinking habit (p=0.008) were more common among HS and diabetes (p<0.001) and dyslipidemia (p=0.002) were more common among IS patients than their counterpart. Most of the patients (222/308, 42%) had their mRS score of 3 to 5 during discharge. Male sex (OR: 1.72, 95% CI: 1.02 to 2.89) and hypertension (OR: 2.20, 95% CI: 1.89 to 3.87) were independently associated with poor outcome on discharge. Conclusion: Most of the patients had moderate to severe disability at discharge. Hypertension is the most important risk factor and predictor of poor outcome. JCMCTA 2022 ; 33 (2) : 18-23